2019
DOI: 10.1371/journal.pone.0216488
|View full text |Cite
|
Sign up to set email alerts
|

Service user, carer and provider perspectives on integrated care for older people with frailty, and factors perceived to facilitate and hinder implementation: A systematic review and narrative synthesis

Abstract: Introduction Older people with frailty (OPF) can experience reduced quality of care and adverse outcomes due to poorly coordinated and fragmented care, making this patient population a key target group for integrated care. This systematic review explores service user, carer and provider perspectives on integrated care for OPF, and factors perceived to facilitate and hinder implementation, to draw out implications for policy, practice and research. Methods Systematic rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
59
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(64 citation statements)
references
References 44 publications
4
59
0
1
Order By: Relevance
“…The Care Act (The Stationary Office, ) is a clear legal framework and places responsibility of addressing carer needs and quality of life on LAs. Implementation towards integrated care is hindered by a lack of continuity and coordination of care and limited involvement of service users and their carers in care decisions (Sadler et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The Care Act (The Stationary Office, ) is a clear legal framework and places responsibility of addressing carer needs and quality of life on LAs. Implementation towards integrated care is hindered by a lack of continuity and coordination of care and limited involvement of service users and their carers in care decisions (Sadler et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Relational continuity was established primarily with the practice matrons. In a recent review of integrated care for older people with frailty, it was found that service users and carers placed importance on continuity of care through one-to-one relationships with a care co-ordinator, valuing this relationship to provide information and support and facilitate personalised care [21]. The main facilitators and maintenance factors for relational continuity, in this study, where the accessibility of the matrons via a direct telephone line and their ability to respond quickly when needed.…”
Section: Primary Care As An Integrated Care Settingmentioning
confidence: 68%
“…There are a growing number of systematic reviews that have evaluated integrated care interventions for frailty. [20][21][22][23][24] Integrated care has been defined as an organisational approach of coordinating continuous care based on a patient's needs and viewing the patient in a holistic manner. 25 All of the systematic reviews on integrated care have considered older people with different levels of frailty as a single population and did not distinguish by frailty status.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%